Experimental calibration of clumped isotopes in siderite between 8.5 and 62 °C and its application as paleo-thermometer in paleosols. (1st June 2019) - van Dijk, Joep; Fernandez, Alvaro; Storck, Julian C.; White, Timothy S.; Lever, Mark; Müller, Inigo A.; Bishop, Stewart; Seifert, Reto F.; Driese, Steven G.; Krylov, Alexey; Ludvigson, Gregory A.; Turchyn, Alexandra V.; et al.
Abstract: The clumped isotope composition of carbonates can be directly related to their formation temperature in the environment, but a robust temperature calibration for siderite is still lacking, and thus limits the applicability of this tool. Here, we present a new calibration for the clumped isotope composition of siderites precipitated with two different techniques between 8.5 and 62 °C: Δ 47 = 0.0428 ± 0.002 ∗ 10 6 T 2 + 0.0683 ± 0.022 ± 95 % C L, T i n K e l v i n R 2 = 0.92 The slope of our calibration obtained at an acid digestion temperature of 115 °C is statistically indistinguishable from recently published calcite and dolomite clumped isotope calibrations. The intercept differs from calcite at phosphoric acid digestion temperatures of 70 and 115 °C due to a difference in phosphoric acid fractionation, highlighting the necessity of a siderite specific calibration. We performed the first survey of the clumped isotope compositions of siderites from different environmental settings at ambient temperatures including two permanently waterlogged swamp sites as modern analogues for pedogenic siderite formation in the geologic record. We conclude that pedogenic siderites form at temperatures between the Mean Annual Air Temperature (MAAT) and the summer air temperature highlighting the strong potential of siderites for paleoclimate reconstructions in continental environments.